System Pharmacological Approach to Investigate and Validate Multitargeted and Therapeutic Effect of Furocoumarins of Apium graveolens L. for Treatment of Kidney Disease - null Yasheshwar; null Gaurav; Rustam Ekkbal; Prem Gupta; Rajendra Gyawali (Advances in Pharmacological and Pharmaceutical Sciences)
Background. System pharmacological approaches play important roles in drug discovery and development and in biomolecular exploration to investigate the multitarget therapeutic effects of phytochemicals for the treatment of acute and chronic ailments. Objectives. The aim of the study was to apply a system pharmacological approach to investigate the multitarget therapeutic effects of furocoumarins of Apium graveolens L. for the treatment of kidney disease. Methods. Several furocoumarins of Apium graveolens were screened from online databases. Network biology and poly-pharmacology analyses were performed to investigate the multitarget therapeutic effect of furocoumarins. The potential metabolites that showed significant interactions with various genes were selected for in silico docking analysis with CASP-3 and SOD proteins. In silico ADME analysis was also performed to investigate the pharmacokinetic behavior of targeted furocoumarins. Results. Out of thirteen furocoumarins selected for analysis, six showed partial or significant interaction with SOD and CASP-3 proteins. These metabolites may alleviate kidney dysfunction by reducing oxidative and inflammatory stress, regulating apoptosis, slowing down the progression of diabetic nephropathy, and reducing hypertension and glomerular vascular rigidity. In silico docking analysis revealed bergapten as a potential therapeutic agent for kidney disease treatment. In silico docking analysis showed anglicine, imperatorin, and sphondin exhibited strong interaction with CASP-3 and SOD with binding energy −6.5, −7.2, −6.5 and −6.8, −6.2 −5.7 kcal/mol, respectively. These components exhibited greater conventional hydrogen bonding with CASP-3 and SOD than other furocoumarins. Furthermore, in silico ADME analysis of metabolites showed that all furocoumarins have a highly lipophilic nature, good skin permeability, and GI absorption, as well as good blood-brain permeability (BBB). Conclusion. Furocoumarins reduce kidney dysfunction and associated pathophysiological complications via the reduction of glomerular vascular rigidity, diabetic nephropathy, and oxidative and inflammatory stress. However, further biomolecular and clinical examinations are necessary to validate and enhance the credibility of present findings.